Narrative Review: Evaluasi Rasionalitas Penggunaan Antibiotik pada Infeksi Saluran Kemih (ISK) di Beberapa Rumah Sakit Indonesia - Vika Rahayu Retnaningtyas; Sri Wahyuningsih (LPPM Institut Pendidikan Nusantara Global, 2026)
Urinary Tract Infection (UTI) is one of the most common infectious diseases encountered in hospitals and is a major cause of antibiotic use. The high use of antibiotics in UTI cases, if not used rationally, has the potential to increase treatment failure and antimicrobial resistance. Therefore, evaluating the rationality of antibiotic use is crucial to assess the alignment of clinical practice with evidence-based therapy guidelines. This research is a descriptive study using a literature review approach. Data were obtained from national scientific articles from 2022–2025 that discussed the evaluation of antibiotic use in patients with UTI in hospitals. Articles were selected based on inclusion criteria that included topic suitability, full-text availability, and evaluation of antibiotic rationality using the Gyssens method or parameters of appropriateness of indication, antibiotic type, dose, interval, and duration of therapy. Data were analyzed descriptively and qualitatively through narrative synthesis. The results of the synthesis indicate that the level of rationality of antibiotic use in UTI cases in Indonesian hospitals remains variable. Several studies reported antibiotic use in accordance with therapy guidelines, but most still found discrepancies in aspects of antibiotic selection, dose, interval, and especially duration of therapy. The predominant use of broad-spectrum antibiotics and Watch-category antibiotics was also found, potentially increasing the risk of resistance. Irrational antibiotic use has been shown to be associated with suboptimal clinical outcomes, particularly in patients with comorbidities. These findings indicate that non-adherence to UTI therapy guidelines remains a major challenge in clinical practice. Regular evaluation of antibiotic use and implementation of antimicrobial stewardship programs in hospitals are needed to improve therapeutic effectiveness and reduce the risk of antimicrobial resistance.